Whole-genome sequencing resources of 301 indigenous Tibetan sheep from the Himalayan region - Jipan Zhang; Yangshen Zhang; Mengying Wang; Gesang Luobu; Zhaxi Duoji; Ciren Pubu; Jikang Zheng; Hong Miao; Yongju Zhao (Scientific Data)
Abstract Compared to commercial sheep breeds, Tibetan sheep are exceptionally productive in high-altitude environments. Whole-genome sequencing can elucidate the genetic markers and candidate genes related to such economic traits, greatly accelerating the breeding progress. However, a lack of genome sequence data has hindered the functional gene dissection and genetic improvement of Tibetan sheep. This study presents whole-genome sequencing data from 301 Gamba sheep, a Tibetan national breed raised in extremely high-altitude regions. The data represents 12.3 Tb paired-end sequences generated on a BGI-T7 platform. An average sequencing depth of 13.8X, an average mapping ratio of 94.0%, and an average genome coverage of 99.6% illustrated the high quality of the sequence data. By aligning the sequence data to the sheep reference genome ARS-UI_Ramb_v3.0 with variants filtration, 39,718,985 single nucleotide polymorphisms (SNPs) and 5,275,473 insertions-deletions (InDels) were obtained. Genetic kinship analysis indicated the sample independence and high quality of the selected individuals. This whole-genome dataset significantly enriches public resources for studying the genetic diversity, genomic selection, and environmental adaptations of sheep.